S134. INCIDENCE, IMPACT AND TRAJECTORIES OF PSYCHOTIC EXPERIENCES FROM CHILDHOOD TO ADULTHOOD, AND PREDICTION OF PSYCHOTIC DISORDER. (18th May 2020) - Zammit, Stanley; Heron, Jon; Rammos, Alexandros; Jones, Hannah; Kounali, Daphne; Sullivan, Sarah; Croft, Jazz; Cannon, Mary; David, Anthony; Fletcher, Paul; Holmans, Peter; Jones, Peter; et al.
Abstract: Background: Given the global burden of disease of psychotic disorders and the promise of benefit from early intervention, there is an imperative to understand the developmental trajectories from onset of psychotic experiences to clinical disorder and to improve identification of individuals at greatest risk. The aims of this study therefore were: 1) to describe, for the first time, the change in incidence of psychotic experiences in the general population from childhood through early adulthood; 2) to describe the prevalence and burden of unmet clinical need of at-risk mental states and psychotic disorder among young adults in the general population; 3) to examine the predictive ability of both self-reported and interviewer-rated measures of psychotic experiences during childhood and adolescence in identifying psychotic disorder by early adulthood; and 4) to describe longitudinal profiles of psychotic experiences from childhood through early adulthood and investigate a comprehensive range of childhood determinants of symptom persistence. Methods: We used data from the ALSPAC birth cohort study. Psychotic experiences and disorder were assessed using semi-structured interviews at ages 12, 18, and 24 (N=7, 900 with any data). Incidence rates were estimated using flexible parametric modeling, and positive predictive values (PPVs), sensitivity, specificity, and area under the curve were estimated for prediction. Longitudinal profiles were constructed based on interviewer ratings and frequency of experiences, with profiles describing no experiences (62.5%), episodic experiences (26.5%), persistent/recurrent low frequency (9.1%), and persistent/recurrent high frequency (1.9%) groups. Multinomial regression was used to examine risk factors for persistence, covering socio-demographic, genetic, behavioural, cognitive, and psychological characteristics during childhood. Results: The incidence rate of psychotic experiences increased between ages 12 and 24, peaking during late adolescence. A total of 109 individuals (2.8%) met criteria for a psychotic disorder up to age 24, of whom 70% had sought professional help. Prediction of current psychotic disorder at age 24 (N=47, 1.2%), by both self-report and interviewer-rated measures of psychotic experiences at age 18 (PPVs, 2.9% and 10.0%, respectively), was improved by incorporating information on frequency and distress (PPVs, 13.3% and 20.0%, respectively), although sensitivities were low. The PPV of an at-risk mental state at age 18 predicting incident disorder at ages 18–24 was 21.1% (95%CI 6.1, 45.6), and the sensitivity was 14.3% (95%CI 4.0, 32.7). Longitudinal profile analysis showed that persistence was highest in those with higher levels of emotional instability and borderline personality traits in childhood, whilst persistence was strongly related to concurrent and increasing levels of social isolation, anxiety, self-harm, and substance use over time. Discussion: Our study results show a peak in incidence of psychotic experience during late adolescence just prior to the peak incidence rate for schizophrenia, and an unmet need for care in young people with psychotic disorders. Although we show the potential efficiency of self-report measures for prediction, because of the low sensitivity, targeting individuals in non-help-seeking samples based only on more severe symptom cutoff thresholds will likely have little impact on population levels of first-episode psychosis. The primary characteristics indexing whether psychotic experiences are likely to persist over time is the presence of emotion regulation difficulties in childhood, providing evidence of a potentially modifiable target for prevention.